ANALISIS IMPLEMENTASI SERTIFIKASI USAHA PARIWISATA BIDANG PERHOTELAN DI KOTA MALANG - Anita Wijayanti; Yusri Abdillah; M. Kholid Mawardi (Jurnal Administrasi Bisnis, 2016)
This study to reviews and analyzes the hospitality industry. Hotel becomes one of the growing tourism industries in Indonesia. Since ASEAN Economic Community (AEC) existence in 2015, hotel certification is used by the government as one of the way to solve global market competition problem. The Indonesian government has already arranged standard of hotel business that should be obeyed by every hotel business. However, it has not responded positively by all hotel businesses in the Malang. There are only 23 hotels from 81 hotels of total amount that have already certified in Malang. There are some reasons why do some hotels in Malang do not processing their certifications yet, such as: certification fee that is assumed as too expensive, there are still some of non-star hotel business which are lack of understanding about hotel certifications, employee competency which are not sufficient yet to fulfill the minimum standard and also there are less of hotel certification socialization. Based on that fact, until this time being, the government only do socialize and provide the guidance of the importance of hotel certification. There are still no administrative sanctions for hotels which have not been certified yet. Key Word: Hospitality, Hotel, Certification, Standardization ABSTRAK Penelitian ini untuk mengkaji dan menganalisis industri perhotelan. Hotel menjadi salah satu usaha pariwisata yang terus berkembang di Indonesia. Dengan adanya Masyarakat Ekonomi ASEAN (MEA) 2015, salah satu hal yang dilakukan oleh Pemerintah agar hotel dapat bersaing dalam pasar global dengan adanya sertifikasi. Pemerintah Indonesia telah menetapkan standar usaha hotel yang harus dipatuhi oleh setiap pelaku usaha hotel. Namun, hal tersebut tidak direspon positif oleh semua pelaku usaha di Kota Malang. Ada 23  hotel dari 81 hotel yang sudah melakukan sertifikasi di Kota Malang. Penyebab pelaku usaha tidak melakukan proses sertifikasi adalah biaya sertifikasi usaha hotel mahal, kurangnya pemahaman pelaku usaha hotel non bintang, sertifikasi kompetensi karyawan belum mencapai batas minimum, dan kurangnya sosialisasi sertifikasi usaha hotel. Upaya yang dilakukan oleh Dinas Kebudayaan dan Pariwisata masih sebatas melakukan sosialisasi atau memberikan pengarahan mengenai pentingnya sertifikat penggolongan hotel. Belum ada sanksi administratif yang dilakukan kepada hotel-hotel yang belum melakukan sertifikasi. Kata Kunci: Perhotelan, Hotel, Sertifikasi, Standardisasi